Exposure to exposure: A protocol for leveraging exposure principles during training to address therapist-level barriers to exposure implementation - Kemp, Joshua; Benito, Kristen; Herren, Jennifer; Brown, Zoe; Frank, Hannah E.; Freeman, Jennifer (Frontiers in Psychiatry, 2023)
Background: Exposure therapy is a highly effective but underutilized treatment for anxiety disorders. A primary contributor to its underutilization is therapist-level negative beliefs about its safety and tolerability for patients. Given functional similarities between anxious beliefs among patients and negative beliefs about therapists, the present protocol describes how exposure principles can be leveraged during training to target and reduce therapist negative beliefs. Methods: The study will take place in two phases. First, is a case-series analysis to fine-tune training procedures that is already complete, and the second is an ongoing randomized trial that tests the novel exposure to exposure (E2E) training condition against a passive didactic approach. A precision implementation framework (Frank et al., 2022) will be applied to evaluate the mechanism(s) by which training influences aspects of therapist delivery following training. Anticipated Results: It is hypothesized that the E2E training condition will produce greater reductions in therapists’ negative beliefs about exposure during training relative to the didactic condition, and that greater reduction in negative beliefs will be associated with higher quality exposure delivery as measured by coding of videotaped delivery with actual patients. Conclusion: Implementation challenges encountered to date are discussed along with recommendations for future training interventions. Considerations for expansion of the E2E training approach are also discussed within the context of parallel treatment and training processes that may be tested in future training trials.